85‐1: Invited Paper: Organic LCDs Using Polarisers as Substrates: Enabling Pixel‐level Dimming in Dual‐Cell LCDs. Issue 1 (25th September 2020) - Harding, James; Cain, Paul; Reeves, Will; Wheeler, May; Banach, Mike
Abstract : A well‐known method of increasing the contrast of an LCD is to use a dual cell. FlexEnable's low temperature organic TFT process allows us to work directly with polarisers as substrates. This reduces the gap between the cells to previously unreachable levels, allowing pixel level dimming and OLED‐like contrast from a simpler stack.